Menjadi Saksi Kristus Di Era Digital - Purdaryanto, Samuel; Daeli, Regueli (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
Becoming a witness of Christ in the midst of the world is a Great mandate given directly by the Lord Jesus Christ before He ascended to heaven. The command to be a witness to the ends of the earth has not been completed until now which has entered the digital era. The command to be a witness must still be carried out so that all ethnic groups become disciples of Christ. Through qualitative research methods, this study describes how to be a witness in the digital era. The results of this study explain what the digital era is, and how to use digital platforms as a means to witness Christ to many people. This study concludes that believers must adapt to being in the digital era by utilizing digital platforms such as social media as a means of witnessing the gospel news. Keywords: Witness, digital era, social media Menjadi saksi Kristus di tengah dunia merupakan mandate Agung yang diberikan langsung oleh Tuhan Yesus Kristus sebelum Ia naik ke surga. Perintah menjadi saksi hingga ujung bumi masih belum tuntas hingga saat ini yang telah memasuki era digital. Perinta menjadi saksi tetap harus dijalan agar semua suku bangsa menjadi murid Kristus. Memalui metode penelitian kualitatif, penelitian ini mendeskripsikan bagaimana menjadi saksi di era digital. Hasil penelitian ini menjelaskan apa itu era digital, dan bagaimana menggunakan platform digital sebagai sarana untuk menyaksikan Kristus kepada banyak orang. Penelitian ini menyimpulkan bahwa oang percaya harus beradaptasi dalam menjadi di era digital dengan memanfaatkan platform digital seperti media sosial sebagai saran dalam menyaksikan berita Injil.